O conceito de “cortiço” na obra literária de Aluísio de Azevedo: contextos sociais, conflitos urbanos e realidades ficcionais - Carlos, Giovana Meireles da Rosa (2024)
The subsequent dissertation discusses the main aspects of the social imaginary and cultural life in the real-naturalist work 'O Cortiço' by Aluísio de Azevedo, published in 1890. In this logic, the concept of tenement, as a collective and homogenizing character of identities, is our research object. We seek to understand the spatiality of collective housing and its multiple dynamics through the study of its characters. In addition to these factors, we explore the main characteristics and debates surrounding this social place. Our research methodology involves the history of ideas linked to social history. Starting from Lacapra's reflections to think about the relationships between history and literature through the literary work, the author states that "[...] a crucial problem for analysis at the intersection of history and literature is how a literary text comes to terms with the pressures of historical events and forces." (LACAPRA, 2013, p. 29). Furthermore, the historical category of modernity in Reinhart Koselleck helps us reflect on Brazil between past, present and future. From this perspective, the aim is to reveal the city's social conflicts, represented by literary writing.